Double-pass versus aberrometric modulation transfer function in green light - Rodríguez, Pablo; Navarro, Rafael (Journal of biomedical optics, 2007)
Intraocular scattering can become an important source of optical degradation in the aging eye. To evaluate its relative contribution to the ocular modulation transfer function (MTF), a compact, dual experimental system comprising a laser ray tracing (LRT) wavefront sensor and a double-pass setup is used. An aberrometric MTF is estimated from aberration measurements, whereas a second MTF is derived from the double-pass point-spread function. While the former only accounts for the effect of aberrations (up to seventh order), the double-pass MTF includes the combined effect of both scattering and aberrations. A 532-nm laser light source is used to minimize choroidal scattering. Measurements are done on 19 normal, healthy eyes from three groups of subjects of different ages. The two MTFs are obtained for a 6-mm pupil diameter and partial refractive compensation. Intraocular scattering is modeled as a random wavefront aberration characterized by its variance and correlation length. These parameters are fitted from the differences between both MTFs. Our results show that double-pass and LRT techniques provide similar MTFs for most normal eyes, although small amounts of scattering, or high-order aberrations, could be measured in some eyes. A gradual increase in intraocular scattering with age is also observed.